Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
ZenodoArchiveID: 4556932 PreviousDOI: 10.5281/zenodo.4477141 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948149 10.5281/ZENODO.4556932 10.5281/zenodo.4477141 10.5281/zenodo.4556932 2259720:DSXFK6JB 2339240:4JRWSL6I 2339240:8YVF7D5N 2339240:EPCMUN8C 2339240:FKFII8IK 2339240:H8YNQIY9 2339240:IJJ6TY76 2339240:QBDJ6U43 2339240:YIAFCN9T 2405685:5GBRDVHP 2405685:65UPSCK3 2405685:67BFM4C5 2405685:6CG6479A 2405685:DM6JSS9K 2405685:P8NUYK3M 2405685:PZHGV2XR 2405685:QBYZW7N2 2405685:RBUXXHAD 2405685:VHGNZV9N 2405685:X8BFH2K5 2405685:YMWE6FR6
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Education during the COVID-19 crisis: opportunities and constraints of using EdTech in low-income countries - David, Raluca; Pellini, Arnaldo; Jordan, Katy; Philips, Toby (Zenodo, 2020)
Key points: Technology can help mitigate the effects of the educational crisis and closures of schools, but ed-tech is not a silver bullet and governments need to have realistic expectations about what it can achieve The digital divide means that internet and mobile network access varies greatly in middle- and low-income countries Governments can provide immediate support by informing teachers about simple grassroots platforms where they can share their own ed-tech solutions Educational TV and radio broadcasts in combination with SMS are effective communication channels between educators and students when the internet connectivity is poor or not available It will be important for education authorities to begin planning how in 12-months’ time they will diagnose and treat the learning gaps that have emerged during the crisis.
shortDOI: 10/ghgnd7 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3750976 10/ghgnd7 2339240:3CKN9C4K 2339240:5AHKKQF6 2405685:92ZVGWNU 2405685:CT8JMZEU
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodoETH; covid-19; crisis education; distance education; education; education policy; educational technology; emergency education; pandemic education; school closures; schools

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

Education in Emergencies: A Rapid Evidence Review - Mitchell, Joel; Ashlee, Amy; Clericetti, Giulia; Gladwell, Jessica; Torrance, Rebecca (EdTech Hub)
PreviousDOI: 10.5281/zenodo.4476897 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4476897 10.5281/zenodo.4556940 2339240:GU8FEH69 2339240:W9GJBGT9 2405685:FEXJQ37Q 2405685:ZPTMAP5C
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
ZenodoArchiveID: 5652036 Dates: 13-11-2020 — Actualizado el 09-01-2021 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652036 10.6018/red.453621 2405685:2BIQKP9C 2405685:IVHRNTQ7 2405685:L7Y5JD68 2405685:ZXQZ3FVV
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
ZenodoArchiveID: 5652092 previousDOI: 10.5281/zenodo.4140104 previousZenodoArchiveID: 4140104 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4140104 10.5281/zenodo.4140104 10.5281/zenodo.4140104; 10.5281/zenodo.5652092 2339240:2K6FG2CF 2339240:2XJTN3MP 2339240:3TNWACL9 2339240:942WVA7N 2339240:DN7NQV5Y 2339240:LKQW3A8S 2339240:MDTPARWA 2339240:PNTVB7PY 2339240:U3838PXA 2339240:XIE9NJ3S 2405685:5DNJGPNU 2405685:BA3K6CK8 2405685:BLRKEEAU 2405685:CCZW4ARW 2405685:DAFBBJ3F 2405685:DP9HJGLT 2405685:HRT8E6US 2405685:RVIEHPP5 2405685:XUVA9827 2405685:Z6UIK8CZ 2405685:ZITF5IDK 2534379:FDZIF5DH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

Parent and Caregiver Engagement in Kenya: Gaps, opportunities, and emerging questions for future research - Flam, Rebekka; Honda, Delanie; Ramesh Vasudevan, Sharanya; Mbugua, Wanjiku (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15352737 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1112 ZenodoArchiveConcept: 15352736
Keywords: _r:AddedByMyEducationEvidence

EdTech in Nigeria: A Rapid Scan. An overview of EdTech policies and interventions in Nigeria with a focus on northern Nigeria - Ramesh Vasudevan, Sharanya; Oyedele, Oluwatomisin (EdTech Hub, 2024)
Commissioned as a Helpdesk request from the FCDO-funded Partnership for Learning for All in Nigeria (PLANE) project, this EdTech Hub rapid scan provides an overview of the EdTech landscape in Nigeria. Given the PLANE programme’s focus on northern Nigeria, this rapid scan also assesses state-level policies and infrastructural challenges in three northern Nigerian states — Jigawa, Kaduna, and Kano. Furthermore, this rapid scan builds on the evidence presented in the previous EdTech Hub rapid scan from 2020, which focused on all states and the situation before the Covid-19 pandemic. Keywords: EdTech; policies; interventions; northern Nigeria; Partnership for Learning for All in Nigeria An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11235144 ZenodoArchiveConcept: 11235143 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1029 10.53832/edtechhub.1030
Keywords: _r:AddedByMyEducationEvidence

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, , Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4917252 10.5281/zenodo.4917252 2339240:G2X4SJI9 2339240:MUSPGK9F 2339240:MVU3QIHM 2339240:NQF22P32 2405685:B2ABXUCR 2405685:D6PWMC4I 2405685:HW7NU96L 2405685:JWIHBL5M 2405685:PXBXCZ29 2405685:YHC5ZPU8
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen